On-Chip Silicon Bragg-Grating-Waveguide-Based Polymer Slot for Gas Sensing - Merna Khafagy; Maira Khafagy; Passant Hesham; Mohamed A. Swillam (Photonics, 2025)
This work presents a novel <semantics>CO2</semantics> gas sensor based on a slotted polymer-phaseshift Bragg grating (SP-PSBG) waveguide filled with polyhexamethylene biguanide (PHMB) as the sensing medium. The transmission resonance, characterized by a narrow peak with a full width at half maximum (FWHM) of 1.6 nm within the Bragg grating bandgap, is highly responsive to refractive index changes in PHMB caused by variations in <semantics>CO2</semantics> concentration. Numerical simulations demonstrate a sensitivity of 14.4 pm/ppm, outperforming conventional gas sensors based on functional material coatings. This enhanced performance comes from the direct interaction between the PHMB-filled resonant structure and the cladding that contains <semantics>CO2</semantics> molecules, eliminating the need for polymer-coated cladding layers. The optimization approach employed in this design focuses on maximizing the optical confinement factor within the PHMB-filled slot, leading to an effective overlap between the guided optical mode and the sensing material.